Textures : pour approfondir la communication orale et écrite - Hall, Elizabeth Berglund; Theobald, Anne (College teacher); Hall, Mark Andrew; Pfrehm, James, 1977- (New Haven : Yale University Press, 2018)
"Language proficiency emerges not solely as mastery of discrete skills, but also through one's ability to express ideas fully in a variety of cultural contexts. This innovative French-language textbook employs a holistic approach that integrates listening, reading, writing, and conversation--placing communication at the heart of the learning experience. It provides intermediate-level students with the interpretive tools necessary for literary and cultural studies. There are interactions with a variety of texts and media, including short stories, poems, essays, images, and podcasts."--
Acknowledgments -- Introduction -- 1. Le dépaysement -- 2. La vie moderne -- 3. Le sport -- 4. La beauté -- 5. La culture de masse -- 6. L'identité -- 7. Les étapes de la vie -- 8. La nature humaine -- 9. La famille -- 10. La critique sociale -- Appendix 1. Qu'en dites-vous? Transcriptions -- Appendix 2. Cité-U Scripts -- Credits.
Includes bibliographical references.
In French with introduction and some notes in English.
Print version record.
JSTOR
Keywords: French language -- Textbooks for foreign speakers -- English; French language -- Grammar; French language -- Spoken French; French language -- Readers; Français (Langue) -- Manuels pour anglophones; Français (Langue) -- Grammaire; Français (Langue) -- Français parlé.; PSYCHOLOGY -- Social Psychology; FOREIGN LANGUAGE STUDY -- French; French language; French language -- Grammar; French language -- Spoken French; Electronic books; Readers (Publications); Textbooks; Textbooks -- for English speakers; Textbooks